2012
DOI: 10.1002/jccs.201200011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oximes with NH2OH.HCl/DOWEX(R)50WX4 System

Abstract: The oximation of a variety of carbonyl compounds was efficiently carried out with DOWEX(R)50WX4/ NH 2 OH·HCl system. The reactions were performed in ethanol to give Z-aldoximation isomers of aldehydes and E-oximaton of acetophenone derivatives in a perfect selectively. The oximation of compounds with two carbonyl groups was carried out selectively on one carbonyl moiety. Also, the oximation of aldehydes over ketones has been accomplished successfully by this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Recently, we have reported that DOWEX(R)50WX4 ion-exchange resin has been used for regioselective synthesis of oximes by NH 2 OH . HCl/DOWEX(R)50WX4 system [51], reduction of a variety of carbonyl compounds such as aldehydes, ketones, α-diketones, acyloins and α,β-unsaturated carbonyl compounds to their corresponding alcohols by NaBH 4 / DOWEX(R)50WX4 system [52], synthesis of cyanohydrins by NaCN/DOWEX(R)50WX4 [53] and reductive-amination of a variety of aldehydes and anilines by NaBH 4 /DOWEX(R)50WX4 [54].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have reported that DOWEX(R)50WX4 ion-exchange resin has been used for regioselective synthesis of oximes by NH 2 OH . HCl/DOWEX(R)50WX4 system [51], reduction of a variety of carbonyl compounds such as aldehydes, ketones, α-diketones, acyloins and α,β-unsaturated carbonyl compounds to their corresponding alcohols by NaBH 4 / DOWEX(R)50WX4 system [52], synthesis of cyanohydrins by NaCN/DOWEX(R)50WX4 [53] and reductive-amination of a variety of aldehydes and anilines by NaBH 4 /DOWEX(R)50WX4 [54].…”
Section: Resultsmentioning
confidence: 99%
“…We have reported a fast and efficient method for the reduction of varieties of carbonyl compounds such as aldehydes, ketones, conjugated aldehydes and ketones, á-diketones and acyloins to their corresponding alcohols under microwave irradiation in water as green solvent 3c . Recently, the oximation methods has been reviewed 4 . The lack of information for systematic the oximation of carbonyl compounds in water under microwave irradiation and our ongoing attentions to the development of modified methods in organic synthesis [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] encouraged us to investigate this transformation with NH 2 OH·HCl under microwave irradiation in water as a green and good solvent for transferring electromagnetic energy into heat and so driving an oximation reaction effectively.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…6,7 Because of some limitations such as low yield of the products, long reaction times and the presence of acid or base sensitive functionalities in aldehyde or ketonic compounds, the classical methods usually are not suitable. In this context, several improvements such as using nano Fe3O4 8 , Cu-SiO2 9 , NH2OH•HCl/K2CO3 10 , Dowex 50WX4 11 , heterogeneous polyoxometalates 12,13 , phase transfer catalysts 14 , basic ionic liquid 1-butyl-3-methylimidazolium hydroxide 15 , NH3/oxidant/catalyst systems [16][17][18][19][20][21] , wet basic Al2O3/microwave 22 , SiO2/ NH2OH/microwave 23 , absence of any catalyst and solvent 24 , CaO/solvent-free 25 , TiO2/SO4 2 − solid super acid 26 , ethylenediamine/oxone 27 , Na2SO4/ultrasound 28 , titanyl acetylacetonate/NH2OH 29 , Bi2O3/ NH2OH•HCl 30 , clay-based titanium silicalite-1 31 , host (dealuminated zeolite Y)-guest (12-molybdo-phosphoric acid) nanocomposite 32 and organo-SOMO catalysis 33 have been reported for the preparation of oximes.…”
Section: Introductionmentioning
confidence: 99%